PENGEMBANGAN KAPASITAS: BIDANG PERLINDUNGAN JAMINAN SOSIAL DINAS SOSIAL KABUPATEN BERAU DALAM PELAKSANAAN PROGRAM KELUARGA HARAPAN SEBAGAI UPAYA PENGENTASAN PENDUDUK MISKIN - Susanti, Endah (PRODI EKONOMI PEMBANGUNAN, STIE MUHAMMADIYAH TANJUNG REDEB, 2018)
This study aims to determine the factors that inhibit the function of Social Security Protection Division (Linjamsos) on the Social Service of Berau District in the implementation of Hope Harvest Program (PKH) as government effort in alleviating poverty and development of Social Security Protection Division (Linjamsos) an effort to strengthen the function of the Social Service of the District of Berau in the context of poverty alleviation. This study uses a qualitative method. The theory used is institutional capacity building theory from Riyadi Soeprapto (2010). The results of this study indicate that Linjamsos Social Service of Berau Regency can not optimally perform its function as the implementer of Family Hope Program (PKH) in efforts to alleviate poor vulnerable population because it still has barriers from the system in the form of lack of commitment of PKH Assistant to implement the rule expressly as legal basis, communication systems, limited facilities and infrastructure, poor road infrastructure, unknowing beneficiary families (KPM) with banking system, and inclusion of errors and exlusion errors in the KPM data validation process.